Design and Development of a Medication Preparation (3 in 1 Medprep) Device for Liquid Vial Dilution in Healthcare Settings - Muhammad Zakwan Zikri Irwan Affandi; Nor Hidayati Diyana Nordin; Muhammad Afif Husman; Aimi Shazwani Ghazali; Siti Noorkhairina Sowtali (INTERNATIONAL JOURNAL OF CARE SCHOLARS, 2026)
Background: The manual preparation of liquid medications in healthcare settings presents significant challenges, including the need for high precision, time-intensive procedures, and the risk of human error, which may compromise patient safety and contribute to physical strain among healthcare workers. 3 in 1 MedPrep is a multifunctional medication preparation system incorporating tablet crushing, tablet cutting, and liquid dilution functions. This study focuses on the development and evaluation of its liquid dilution function. Methods: The development of 3 in 1 MedPrep, specifically its liquid dilution function followed a structured five-phase methodology comprising expert consultation, system design with engineering calculations, mechanical prototyping, and testing with 30 mechanism trials and comprehensive dry runs of the fully integrated system. Results: The liquid dilution function of 3 in 1 MedPrep integrates three primary mechanisms: (i) syringe extraction mechanism (ii) vial piercing mechanism and (iii) mixing mechanism. Testing across 30 cycles demonstrated strong performance, with syringe extraction achieving 99.22% precision, vial piercing achieving 98.85% precision with 100% success, and mixing reaching 100% solubility success. Overall, the fully integrated system operated reliably with an aggregate precision of 99.9%. Conclusion: 3 in 1 MedPrep demonstrates strong potential to enhance efficiency, accuracy, and safety in medication preparation within healthcare settings. Further development incorporating sensor-based closed-loop feedback, sterilisation integration, and regulatory clinical certification is recommended to support clinical translation.